Redox behaviour of crystalline lifepo4 prepared by chemical precipitation and low temperature sterilisation - Kufian, M.Z.; Arof, Abdul Kariem; Sanusi, A.; Basirun, Wan Jefrey (Springer Verlag (Germany), 2009)
The phospho-olivine LiFePO4 was successfully prepared by chemical precipitation and steriliser heating in the absence of nitrogen gas and reducing agent. The samples were characterised by XRD and SEM. The average particle size of the sample obtained in this work was 58.3 nm. Cyclic voltammetry exhibited a pair of redox peaks associated with the Li+ ion insertion and de-insertion in LiFePO4. Electrochemical behaviour of LiFePO4 at different scan rates is also discussed in this paper.